Construction and Virulence of Filamentous Hemagglutinin Protein B1 Mutant of Pasteurella multocida in Chickens - Dong-chun GUO; Yan SUN; Ai-qin ZHANG; Jia-sen LIU; Yan LU; Pei-xin LIU; Dong-wei YUAN; Qian JIANG; Chang-de SI; Lian-dong QU (Journal of Integrative Agriculture, 2014)
Pasteurella multocida, a Gram-negative nonmotile coccobacillus, is the causative agent of fowl cholera, bovine hemorrhagic septicemia, enzoonotic pneumonia and swine atropic rhinitis. Two filamentous hemagglutinin genes, fhaB1 and fhaB2, are the potential virulence factors. In this study, an inactivation fhaB1 mutant of P. multocida in avian strain C48-102 was constructed by a kanamycin-resistance cassette. The virulence of the fhaB1 mutant and the wild type strain was assessed in chickens by intranasal and intramuscular challenge. The inactivation of fhaB1 resulted in a high degree of attenuation when the chickens were challenged intranasally and a lesser degree when challenged intramuscularly. The fhaB1 mutant and the wild type strain were investigated their sensitivity to the antibody-dependent classical complement-mediated killing pathway in 90% convalescent chicken serum. The fhaB1 mutant was serum sensitive as the viability has reduced between untreated serum and heat inactivated chicken serum (P<0.007). These results confirmed that FhaB1 played the critical roles in the bacterial pathogenesis and further studies were needed to investigate the mechanism which caused reduced virulence of the fhaB1 mutant.